Consideration of future consequences and alcohol use among Northern Irish adolescents. (October 2013) - Mckay, Michael T; Percy, Andrew; Cole, Jon C.
<x xml:space="preserve">Abstract</x> This study investigated the relationship between consideration of future consequences and alcohol use among adolescents. A cross-sectional design was used and a large sample of 12- to 16-year-old schoolchildren (n = 806) in Northern Ireland were recruited for this study. Alcohol use was assessed using a composite measure of drinking behaviour, the Adolescent Alcohol Involvement Scale. Time perspective was measured using the Consideration of Future Consequences Scale (CFCS). Data were also gathered on self-esteem, three domains of self-efficacy and aggression, all of which have been found to be related to both drinking behaviour and time perspective. Factor analysis of the CFCS revealed support for a two-factor solution, with CFC-I representing present orientation and CFC-F representing future orientation. After controlling for year in school (proxy for age) and gender and for clustering at school level, scores on both subscales were significantly associated with alcohol use. Only CFC-F score remained significant with the addition of psychosocial variables. These results support recent findings of a significant relationship between CFCS score and alcohol use in UK adolescents and University undergraduates, and suggest that in more fully controlled analyses, future orientation, rather than present, is related to adolescent drinking. Results are discussed in relation to health promotion.